Ethics in context: essential flexibility in an international photo-elicitation project with children and young people. Issue 1 (2nd January 2020) - Burningham, Kate; Venn, Susan; Hayward, Bronwyn; Nissen, Sylvia; Aoyagi, Midori; Hasan, Mohammad Mehedi; Jackson, Tim; Jha, Vimlendu; Mattar, Helio; Schudel, Ingrid; Yoshida, Aya
ABSTRACT: Existing literatures have discussed both ethical issues in visual research with young people, and the problems associated with applying 'universal' ethical guidelines across varied cultural contexts. There has been little consideration, however, of specific issues raised in projects where visual research is being conducted with young people simultaneously in multiple national contexts. This paper contributes to knowledge in this area. We reflect on our experiences of planning and conducting the International CYCLES project involving photo elicitation with young people in Bangladesh, Brazil, India, Japan, New Zealand, South Africa and the UK. While some issues such as varying access to technology for taking and sharing photos and diverse cultural sensitivities around the use of photography were anticipated in advance, others were more unexpected. Balancing the need for methods to be appropriate, ethical and feasible within each setting with the desire for sufficient consistency across the project is challenging. We argue that an 'ethics in context' approach and an attitude of 'methodological immaturity' is critical in international visual research projects with young people.